Preconcentration of Metal Ions Using Silica Gel 60 F254 - Svraka, Irnesa; Memić, Mustafa; Sulejmanović, Jasmina; Muhić-Šarac, Tidža (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
In this study, the use of a column packed with unmodified activated silica gel as sorbent for preconcentration of Cd, Co, Cr, Cu, Fe, Mn, Ni and Pb prior to their analysis by flame atomic absorption spectrometry (FAAS) was described. Factors affecting the preconcentration of analytes such as pH, sample flow rate and volume from pure multielement aqueous solutions of known concentration, were determined. The recovery values of prepared samples of known concentration of analytes were: 87.7% (Cd), 94.3% (Co), 95.7% (Cr), 91.2% (Cu), 105.2 % (Fe), 84.5 % (Mn), 96.6% (Ni) and 101.7% (Pb), under the optimum conditions (pH; 9, sample flow rate; 6mL/min, preconcentration factor; 10). The adsorption capacity of unmodified silica gel for Cd, Co, Cr, Cu, Fe, Mn, Ni and Pb was found to be 6.05, 11.54, 13.08, 10.70, 12.18, 12.38, 11.59 and 3.28 µmol /g of adsorbent, respectively. Detection limits of the method were 4.3, 35.0, 58.2, 18.5, 37.1, 10.3, 38.8 and 55.0 μg/L for Cd, Co, Cr, Cu, Fe, Mn, Ni and Pb, respectively.